The impact of corporate governance on the financial, governance and social disclosures at Islamic banks in Malaysia - Marsidi, Asri; Annuar, Hairul Azlan; Abdul Rahman, Abdul Rahim (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia (IIUM)., 2018)
The study examines the impact of board and audit committee on the disclosure of Islamic financial and social reporting (IFSR) among Islamic banks in Malaysia. Drawing on surveys this study seeks the views of accountants working in Islamic banks regarding the importance of items in the IFSR index developed by Marsidi et al. (2016). The annual reports are thereafter used to examine the score of the IFSR for the Islamic banks as well as to collect the data for the related variables. The multivariate regression findings suggest that board size is a significant factor in explaining the IFSR at Islamic banks in Malaysia. Such finding indicates that the size of board, which is represented by the number of directors who sit on the board of directors, is a crucial governance mechanism in achieving the aims of Islamic banks. The result also meets the role of corporate governance from the perspective of Islamic agency theory. The results of the study should not be generalised to year’s prior, or after, the years of examination. The finding is perceived as contributing towards the suitable formation of board of directors specifically in terms of the total number of directors with respect to the financial, governance and social disclosures at Islamic banks. The study uses the Islamic agency theory to explain the governance practices and IFSR disclosures within the context of Malaysian Islamic banks. As such, the paper contributes towards the development and sustainability of Islamic banks both in Malaysia and throughout the globe.